Checklists and clinical governance: learning from the NHS. Issue 8 (1st September 2016) - Oxtoby, Catherine; Mossop, Liz
Abstract : As healthcare professions, medicine and veterinary medicine share many similarities. While the knowledge base and skills required may have fundamental species differences, the delivery of clinical care by vets and doctors is a very similar process, be it to a human or an animal. Here Catherine Oxtoby and Liz Mossop discuss clinical governance and the use of checklists in human medicine and the lessons for veterinary practice. A second article, to be published in a forthcoming issue of In Practice, will look at how checklists can be applied in a veterinary context.